TOTAL PHENOLIC CONTENT, CELLULAR ANTIOXIDANT ACTIVITY AND POTENTIAL HEPATOPROTECTIVE EFFECT OF FRUIT EXTRACTS - Chunhabundit, Rodjana; Kongkachuichai R; Norasing J; Visetpanich Y (Thai Journal of Toxicology, 2020)
Environmental pollutants are sources of several reactive oxygen species and other byproducts of oxidative stress. Such products involve the underlining processes of chronic diseases, either at the initial or progressive stages of the diseases. The antioxidant nutrients and related bioactive compounds common in vegetables and fruits have become a beneficial alternative to prevent oxidative stress in cells. The present study was done to investigate cellular antioxidant activity as well as total phenolic content of the extracts of selected fruits: strawberry, carambola, guava, longkong, pomelo, and tangerine. The protective effect of these fruits on H2O2 induced cytotoxicity was also evaluated in human liver carcinoma cell line (HepG2). Cellular antioxidant activity (CAA) assay was the measurement the ability of antioxidants in fruit extracts to prevent oxidation of cell membrane lipids and production of more radicals in cells. The cytoprotective potential was assessed by using MTT assay. The results showed that strawberry, carambola, and guava had higher phenolic contents than longkong, pomelo, and tangerine. The antioxidant efficacies of fruits in CAA values were consistent with their phenolic contents except longkong which exhibited the highest CAA even contained low level of phenolics. However, cell viability measured after co-treatment H2O2 with the fruit extracts showed the similar cytoprotective ability of all fruit extracts. The present study demonstrates that all selected fruit extracts have protective effect on H2O2 induced oxidative damage in human hepatocarcinoma cells and this effect is related to their cellular antioxidant properties.